Analysis Of The Effect Of Incentives And Work Facilities On Work Motivation And Its Impact On Employee Performance - Dharmawana, Donny; Anwar, M.; Alatas, Abd. Rahman; Judijanto, Loso; Nainggolan, Hermin (International Journal of Artificial Intelligence Research, 2024)
This study aims to analyze the effect of incentives and work facilities onwork motivation and its impact on employee performance at PT. KLMNin Jakarta. The approach used is quantitative with data collectionthrough questionnaires. The research sample was 127 respondentsselected using census techniques. Data analysis was carried out usingthe Structural Equation Model (SEM) method based on Partial LeastSquare (PLS) with the help of SmartPLS software version 3.2.9. Theresults of the study indicate that incentives, work facilities, and workmotivation directly have a positive and significant effect on employeeperformance. In addition, the provision of incentives and work facilitiesalso have a positive and significant effect on employee performanceindirectly through work motivation as an intervening variable